(untitled) (Global Journal of Science Frontier Research, 2023)
This review discusses how we use the most common and novel synthesized active methylene compounds as well as heterocycles having active methyl or methine in the syntheses of a wide variety of substituted and fused pyridines interesting medical and pharmaceutical importance. Many synthetic approaches were used for the preparation of target heterocyclic systems such as cyclocondensation reactions, ring opening-ring closure, cycloaddition, acid-or base-catalyzed reaction, intermolecular cyclization and self-condensation have been reviewed in this paper. Also, the antimicrobial activity carried out on some newly selected synthesized pyridines and their fused derivatives were reported.